2012
DOI: 10.1134/s1063074012030042
|View full text |Cite
|
Sign up to set email alerts
|

Asexual reproduction, evisceration, and regeneration in holothurians (Holothuroidea) from Nha Trang Bay of the South China Sea

Abstract: Peculiarities of asexual reproduction, evisceration, and regeneration were studied in 13 holothu rian species of the orders Dendrochirotida and Aspidochirotida from Nha Trang Bay of the South China Sea. Asexual reproduction by fission has been described for the first time for Cladolabes schmeltzii. It has been shown for the first time that transected C. schmeltzii and Colochirus robustus successfully regenerate not only their anterior, but also their posterior structures. It was found that Pseudocolochirus vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 16 publications
0
45
0
Order By: Relevance
“…Evisceration has generally been considered to occur through the anterior in dendrochirotids (Byrne, 1985), although posterior evisceration has also been documented in Pseudocolochirus violaceus under highly stressful conditions (Dolmatov et al, 2012). Contrary to many dendrochirotids, evisceration in Phyrella occurs posteriorly.…”
Section: Discussionmentioning
confidence: 99%
“…Evisceration has generally been considered to occur through the anterior in dendrochirotids (Byrne, 1985), although posterior evisceration has also been documented in Pseudocolochirus violaceus under highly stressful conditions (Dolmatov et al, 2012). Contrary to many dendrochirotids, evisceration in Phyrella occurs posteriorly.…”
Section: Discussionmentioning
confidence: 99%
“…This discharged mucous helps to prevent the animal from their predator. Adult H. scabra lacking this defensive mechanism develops the similar kind of structure which serves the same function in the coelom (peri-visceral coelom) (Bai, 1971;García-Arrarás and Greenberg, 2001;Murphy et al, 2011;Dolmatov et al, 2012). These two adaptive animal defense mechanisms may explain adaptation at the cellular levels of each individual species of holothuroidea as how the animals respond to its surrounding environments and defense themselves against the harmful pathogens or invading microbes.…”
Section: Discussionmentioning
confidence: 95%
“…Studies of regeneration abilities are important to develop cultivation technologies and increase holothurian populations as reported by Dolmatov (2014). Regeneration of the internal organs after fission has been described in varying degrees of details for 6 holothurian species: H. difficilis (Deichmann, 1922), H. parvula (Emson and Mladenov, 1987), H. atra (Boyer, Cailasson, & Mairesse, 1995;Conand, 1996), H. leucospilota (Conand, Morel, & Mussard, 1997), S. chloronotus (Conand, Armand, Dijoux, & Garryer, 1998), and C. schmeltzii (Dolmatov, Khang, & Kamenev, 2012). Precedence of H. polii mouth formation indicated that P regeneration rate was faster than A.…”
Section: Discussionmentioning
confidence: 99%
“…This variation may be also due to the difference in geographical locations besides differences in sample size, ambient temperature and rearing method. However, many holothurian species regenerate within shorter period such as H. scabra which required only 7 days (Bai, 1971); H. glaberrima with 20-30 days regeneration period (Garcı´a-Arrara´s et al, 1998);and H. atra, H. leucospilota, H. edulis, and H. hilla that completed the gut regeneration for both parts by 40-50 days post fission induction (Dolmatov, Khang, & Kamenev, 2012). On the other hand, the longest recorded period for gut regeneration was for Stichopus mollis which need 145 days (Dawbin, 1949).…”
Section: Discussionmentioning
confidence: 99%